PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN KONSUMEN PADA PROGRAM BURSA NIAGA DI PT RIAU MEDIA TELEVISI - Aqsa, Muhammad Ali; Suri, Kartika (Eko dan Bisnis: Riau Economic and Business Review, 2016)
Competition in the business world in the field of multimedia information, making all areas of the business sector in particular should be able to create quality multimedia services to improve customer satisfaction in the field of multimedia. The purpose of this study aims to determine the effect of service quality which consists of tangible, reliability, responsiveness, assurance and empathy simultaneously towards customer satisfaction at the Commercial Exchange Program in PT Riau Media Television. Samples in this study amounted to 99 people who represent the users of commercial exchange program at PT. Riau Media Television. The sampling technique in this experiment that is using random sampling method in which samples were taken at random. Then for data analysis used descriptive and quantitative analysis using multiple linear regression. Based on the partial results of hypothesis testing, of the five variables that researchers do research, responsiveness  variable is the most dominant variables to influence 28.3% with 7.146 t count.>. t table 1.9858 with a significance level of 0.000  < 0.05. while the variable that does not affect the reliability of variables did not significantly affect customer satisfaction in PT. Riau Media Televisi, it can be seen from the t value 0.460 <1.9858  with significance level 0.647 > 0.05 and Empathy variables with t 1,977 <1.9858 with a significance level of 0.051 > 0.05. Based on the test results the coefficient of determination, it can be concluded that the quality of service that consists of tangible, reliability, responsiveness, assurance and empathy have a significant influence on consumer satisfaction on PT. Riau Media Television with a percentage effect of 67.6%. while the remaining 32.4% is influenced by other variables not examined in this study